2022
DOI: 10.1186/s12864-022-08302-4
|View full text |Cite
|
Sign up to set email alerts
|

The potential use of mitochondrial ribosomal genes (12S and 16S) in DNA barcoding and phylogenetic analysis of trematodes

Abstract: Background Genetic markers like the nuclear ribosomal RNA (rRNA) genes, internal transcribed spacer regions, mitochondrial protein-coding genes, and genomes have been utilized for molecular identification of parasitic trematodes. However, challenges such as the design of broadly applicable primers for the vast number of species within Digenea and the genetic markers’ ability to provide sufficient species-level resolution limited their utility. This study presented novel and broadly applicable p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 72 publications
(88 reference statements)
3
16
0
Order By: Relevance
“…We showed that parasitic nematodes belonging to the four clades (clades I, III, IV, and V), trematodes belonging to three orders (Plagiorchiida, Echinostomida, and Strigeida), and cestodes in two orders (Cyclophylllidea and Diphyllobothridea) were able to be successfully detected. Our results are congruent with Chan et al (2020, 2022), where the same parasitic nematodes and trematodes were able to be identified via Sanger sequencing using the mitochondrial rRNA gene primers 29 , 30 . Through targeting a broad range of helminth species added in the mock communities, we validated that these primers can be applicable for various types of helminth DNA metabarcoding studies targeting different hosts and environment types.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We showed that parasitic nematodes belonging to the four clades (clades I, III, IV, and V), trematodes belonging to three orders (Plagiorchiida, Echinostomida, and Strigeida), and cestodes in two orders (Cyclophylllidea and Diphyllobothridea) were able to be successfully detected. Our results are congruent with Chan et al (2020, 2022), where the same parasitic nematodes and trematodes were able to be identified via Sanger sequencing using the mitochondrial rRNA gene primers 29 , 30 . Through targeting a broad range of helminth species added in the mock communities, we validated that these primers can be applicable for various types of helminth DNA metabarcoding studies targeting different hosts and environment types.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, the 12S and 16S platyhelminth primers recovered a single cercaria of S. mekongi present in the pond water mock helminth community. Our results support the recent findings by Chan et al (2022), where the high sensitivity of the mitochondrial 12S and 16S primers was revealed by successfully amplifying all representative trematode specimens of various life-cycle stages for DNA barcoding 30 . As research on platyhelminth DNA metabarcoding remains relatively unexplored, apart from the study by Douchet et al (2021), having a highly sensitive primer for platyhelminth detection can be helpful 31 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations